PEMBERDAYAAN PEMUDA MELALUI PROGRAM KEWIRAUSAHAAN PEMUDA - Merry Andriany E01106003 Andriany E.01106003 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Youth empowerment is an effort to improve their ability in order to be young entrepreneurs to overcome unemployment. The participation and role of youth could be done by developing and creating employment opportunities, supporting a conducive environment for central development of young entrepreneurship, producing creative and innovative products and services which have economic value and are able to empower local potential, and as a result the quality life of youth and the society is improved. Youth entrepreneurship aims to create job opportunities therefore it should be managed in a good program. The Youth Entrepreneurship Program is a program that rises soul and spirit of business in making youth who has good character, good capacity, competitive and professional. The youth is able to understand their own potential as young entrepreneur, to know business potential in their region, to understand business management techniques, to make businesses network, and to understand business development. The Youth Entrepreneurship Program has two phases; that is Young Entrepreneurship Training and Technical Guidance for Young Entrepreneur where this program can be as knowledge, skills, lifeskills, self improvement, job opportunities. From this program the youth is able to know potential they have in order to be young entrepreneurs that can improve creativity and innovation in business.Keywords : Youth   Unemployment, Youth  Empowerment,  Entrepreneurship  Program, Young Enterpreuneur